Blood work - Connelly, Michael (London : Orion Books, 1998)
Retired FBI agent Terry McCaleb receives a heart transplant, then investigates the death of the woman who donated her heart to him.
National College of Business and Arts
Keywords: Private investigators -- Fiction; Detective and mystery fiction